Penerapan Aloritma Punctured Elias Code Pada Aplikasi Kompresi Short Message Service (SMS) - Juleha Juleha; Guidio Leonarde Ginting; Fadlina Fadlina (JURIKOM (Jurnal Riset Komputer), 2020)
Cellphone technology (handphone) as a means of communication at this time has changed the way people perceive communication. Communication is conveyed in various ways to interpret it, namely in the form of digital images, sound and text. Therefore, we need an application that can assist users in dealing with many people, namely the Short Message Service. This is an input to make things easier for people in a positive way. Short Message Service (SMS) is a basic service that allows the exchange of short text messages between subscribers. SMS at this time is outdated compared to other messenger applications. But there are still some people who still use SMS, especially those who live in rural areas or remote areas because of their limited internet network. Because the cost of sending a single sms is relatively expensive, it is necessary to compress the sms. Compression is the process of minimizing the size of data or files by reducing repetitive data without reducing the quality of the data. Where in this compression it will be linked into an Algorithm, namely the Punctured Elias Code Algorithm. Punctured Elias Code algorithm is an algorithm that consists of the original data plus a number of check bits. If several check bits are omitted, to shorten the series of code, the resulting code is designated punctured.